Incidencia de la metodología en el proceso de aprendizaje de la lecto-escritura en estudiantes de segundo (2015)
The main objective of this research is to describe the impact of the methodology in the learning process of reading and writing in the second grade students of an educational institution in the city of Barranquilla. The various theories of learning and new contributions of the constructivist approach to teaching reading and writing are analyzed. The implemented methodology is descriptive design with ethnographic techniques such as observation: No participatory and rubric model. Finally, an analysis of the findings, which could corroborate the impact of different methodological approaches in the process of literacy learning.